2017
DOI: 10.1016/j.jneuroim.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Virus entry and replication in the brain precedes blood-brain barrier disruption during intranasal alphavirus infection

Abstract: Viral infections of the central nervous system (CNS) are often associated with blood-brain barrier (BBB) disruption, yet the impact of virus replication and immune cell recruitment on BBB integrity are incompletely understood. Using two-photon microscopy, we demonstrate that Venezuelan equine encephalitis virus (VEEV) strain TC83-GFP, a GFP expressing, attenuated strain with a G3A mutation within the 5′ UTR that is associated with increased sensitivity to type I interferons (IFNs), does not directly impact BBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…1d and Supplementary Fig. 1) that showed widely distributed strong positive staining around the capillaries in the cortex as previously reported by others (23).…”
Section: Zikv Infection Of the Choroid Plexus And The Meninges Precedsupporting
confidence: 87%
“…1d and Supplementary Fig. 1) that showed widely distributed strong positive staining around the capillaries in the cortex as previously reported by others (23).…”
Section: Zikv Infection Of the Choroid Plexus And The Meninges Precedsupporting
confidence: 87%
“…Astrocytes and neurons are the primary targets of VEEV in the brain (Cain et al, 2017) inducing well-characterized cytopathic effects in neurons of the CNS. In this study, we showed that VEEV replication in human primary astrocytes and the apoptosis induced following VEEV infection can be suppressed by blocking either ERK or PERK pathways, both of which are responsible for upregulating EGR1 pathway, rescuing the cells from VEEV induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded at a density of 10 [4] cells per 100 µl in 96-well plates overnight, followed by the addition of DMEM with TC-83 (MOI of 2). The cells were incubated for 1h at 37.1°C.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1% of all infections develop into severe encephalitic illness, which can result in coma and death. These deleterious outcomes are most closely associated with aerosol exposure, which allows the virus to quickly enter the brain via the olfactory nerve, where it can establish a robust infection [46]. Neuronal cells are highly permissive to VEEV infection, resulting in rapid viral dissemination, widespread neuroinflammation, and destruction of the blood brain barrier (BBB) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation